Early‐life childhood obesity risk prediction: A Danish register‐based cohort study exploring the predictive value of infancy weight gain. Issue 10 (29th March 2021) - Rotevatn, Torill Alise; Mortensen, Rikke Nørmark; Ullits, Line Rosenkilde; Torp‐Pedersen, Christian; Overgaard, Charlotte; Høstgaard, Anna Marie Balling; Bøggild, Henrik
Summary: Background: Information on postnatal weight gain is important for predicting later overweight and obesity, but it is unclear whether inclusion of this postnatal predictor improves the predictive performance of a comprehensive model based on prenatal and birth‐related predictors. Objectives: To compare performance of prediction models based on predictors available at birth, with and without information on infancy weight gain during the first year when predicting childhood obesity risk. Methods: A Danish register‐based cohort study including 55.041 term children born between January 2004 and July 2011 with birthweight >2500 g registered in The Children's Database was used to compare model discrimination, reclassification, sensitivity and specificity of two models predicting risk of childhood obesity at school age. Each model consisted of eight predictors available at birth, one additionally including information on weight gain during the first 12 months of life. Results: The area under the receiving operating characteristic curve increased from 0.785 (95% confidence interval (CI) [0.773‐0.798]) to 0.812 (95% CI [0.801‐0.824]) after adding weight gain information when predicting childhood obesity. Adding this information correctly classified 30% more children without obesity and 21% with obesity and improved sensitivity from 0.42 to 0.48. Specificity remained unchanged at 0.91. Conclusion: Adding infancy weight gain information improves discrimination, reclassification and sensitivity of a comprehensive prediction model based on predictors available at birth.